The killing spell - Kauwe, Shay (Saga Press, 2026)
In this spellbinding fantasy debut set in a future where language magic reigns, a young Hawaiian woman must solve a murder to clear her name. Kea Petrova is dealing with more than her fair share of trouble. At just twenty-five years old, she's the youngest of five Hawaiian clan leaders living on the Homestead in outer Los Angeles. Nearly 200 years ago, when a catastrophic flood submerged the Hawaiian islands and unleashed magic into the world, these clans forged a treaty with the city, establishing a new Hawaiian homeland. But that treaty is about to expire. Kea struggles to keep her small clan afloat, scraping together rent each month through odd jobs and selling her own crafted Hawaiian language spells. While her talent for language magic is her saving grace, she feels like a shadow of those who came before her. Just when she thinks things can't get any more complicated, the murder of Angelo Reyes--LA's most prominent Filipino activist--turns her world upside-down. Angelo was killed by a death spell--something that, due to the properties of each school of language magic, can only exist in Hawaiian. With independent spellsmithing being technically illegal, Kea quickly becomes the prime suspect, known for her spellwork on the Homestead. To clear her name, she must unravel the mystery behind Angelo's murder and confront LA's most powerful (and dangerous) players, each wielding their own type of magic. The clock is ticking--can Kea save herself, her clan, and the Homestead before it's too late?